ANALISIS FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN GANGGUAN PENGLIHATAN PADA PEKERJA PENGELASAN DI PT MILANO, KECAMATAN TORGAMBA - Ginting, Evfy Septriani (Jurnal Penelitian Kesmasy, 2025)
Efforts in occupational safety and health (OSH) are directed at preserving workers' overall well-being, encompassing physical, mental, and social aspects. Illnesses that develop due to specific job roles or the working environment are categorized as occupational diseases. One common issue is visual impairment, which may emerge when the eyes are forced to work beyond their capacity in unfavorable visual conditions, leading to a decline in sight function. This research investigates the factors that may lead to vision problems among welders employed at PT Milano, situated in Torgamba District, South Labuhan Batu Regency. The study employs a qualitative approach, involving all 30 workers at the company, selected using a total sampling method. Data on visual health were obtained through interviews and questionnaire-based assessments. Findings from the Chi-Square statistical test revealed a meaningful relationship between the use of Personal Protective Equipment (PPE) and work duration with incidents of visual impairment. PPE usage (p = 0.008; α = 0.05; OR = 26.654) and years of service (p = 0.001) showed significant associations. However, variables like age (p = 0.513), duration of employment (p = 0.729), and overall work experience (p = 0.337) did not show a statistically significant link. To help prevent visual health problems and minimize work-related illnesses, the use of proper personal protective gear is strongly encouraged for all workers in welding operations.